Comparison of Ionospheric Total Electron Content Measurements with IRI- 2012 Model Predictions Over Athens - A. Mohammed, Fahmi. (Iraqi Journal of Science, 2023)
Total Electron Content measurements derived from Athens station ionograms (ITEC),located near Iraq, during the ascending phase of solar cycle 24 (July 2009- April 2010),according to availability of data, are compared with the latest version of the InternationalReference Ionosphere model, IRI-2012 (IRI TEC), using two options (NeQuick, IRI01-Corr) for topside electron density.The results obtained from both (ITEC and IRI TEC) techniques were similar, wherecorrelation coefficients between them are very high. Generally, the IRI predictionsoverestimate the ITEC values.